Fourteen Taxa of Angiosperms as New Distributional Records for Central India - Tiwari, Arjun Prasad; Shaikh, Mujaffar; Magesh, Chelliah Raj (Indian Forester, 2018)
The present paper deals with the fourteen taxa of angiosperms as new distributional record for Central India (Madhya Pradesh and Chhattisgarh) based on authors own collections as well as studies of herbarium specimens housed at Central National Herbarium, Howrah (CAL) and Botanical Survey of India, Central Regional Centre, Allahabad. Correct nomenclature with citation, brief description, phenology, habitat, distribution and other field details are provided.